2022
DOI: 10.1037/rep0000446
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between number of disability-related conditions and stigma among U.S. adults.

Abstract: Purpose/Objective Research: Stigma is a common experience for people with disabilities. Stigmatization may lead to disparities in education, employment, and health care, quality of life, and psychological distress. This study’s purpose was to (a) determine the relationship between number of disability conditions and stigma for adults with disabilities; and (b) examine whether identifying as a person with a disability, noticeability of a disability or gender moderate relationship between number of disability co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…Proximal minority stress, a form of self-stigma, was associated with quality of life functioning for sexual minority persons living with CIDs. This finding is consistent with other studies that found various forms of stigma were associated with the quality of life for persons living with CIDs (Char & Bogart, 2022; Degnan et al, 2021; Logie et al, 2018; Mayor et al, 2022) and sexual minority persons (Austin et al, 2017; Fredrick et al, 2020). In this study, internalized heterosexism negatively predicted intrapersonal functioning, such as one's ability to engage in activities of daily living (e.g., walking, grooming, bathing, dressing, toileting, etc.).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Proximal minority stress, a form of self-stigma, was associated with quality of life functioning for sexual minority persons living with CIDs. This finding is consistent with other studies that found various forms of stigma were associated with the quality of life for persons living with CIDs (Char & Bogart, 2022; Degnan et al, 2021; Logie et al, 2018; Mayor et al, 2022) and sexual minority persons (Austin et al, 2017; Fredrick et al, 2020). In this study, internalized heterosexism negatively predicted intrapersonal functioning, such as one's ability to engage in activities of daily living (e.g., walking, grooming, bathing, dressing, toileting, etc.).…”
Section: Discussionsupporting
confidence: 93%
“…Quality of life is a highly relevant construct for persons living with CIDs (Busija et al, 2017) and sexual minority persons DISPENZA 2 (Vosvick & Stem, 2019). Further, and to varying degrees, stigma is associated with the quality of life for those living with multiple CID conditions (Char & Bogart, 2022;Degnan et al, 2021;Logie et al, 2018;Mayor et al, 2022). Additionally, researchers have reported a relation between stigma and quality of life for sexual minority persons (Austin et al, 2017;Fredrick et al, 2020).…”
Section: Quality Of Life Functioningmentioning
confidence: 99%